تقييم الأداء المصرفي: دراسة عملية عن المصارف التجارية الليبية - فاخر مفتاح بوفرنة; ادهم عبد المولى البرغثي; إيهاب حمزة المسماري (Scientific Journal of University of Benghazi, 2018)
This paper aims to evaluate the performance of the Libyan banks by using CAMEL model. To achieve the objectives of this paper, data was extracted from financial statements of four Libyan commercial banks over the time period from 2004 to 2010. The results show that the Libyan banks have, an average, 1.5 points out of 4 on the CAMEL scale, which is less than 2 points. These results expressed that the bank performance is good according to CAMEL model.Whilst this study demonstrates the evaluation of the performance of the Libyan banks by using CAMEL model, it has focused only on the big four Libyan commercial banks. Consequently, even though commercial banks have many similarities, the generalizability of this study is limited. Wider research of other contexts within Libya is needed to illuminate further the influence of size, and ownership factors.